INCLUSIVE EDUCATION AND EXCELLENT EDUCATION: A STUDY ON THE THEME - Regina Ribeiro de Araújo Medeiros , Leize (Revista Gênero e Interdisciplinaridade, 2023)
The present article has as objective to carry out a bibliographical survey on the history of education regarding school exclusion and the search for the socio-educational inclusion of students who need specialized accompaniment for an inclusive education that allows the true inclusion of the individual in the social environment to which this is inserted as the protagonist of this process of legal claim of their rights. In this way, we tried to bring up a different perspective and with new approaches to the teachers involved in this process so that they are prepared and oriented with technical basis to experience this new demand in the educational context of Brazil.